2021
DOI: 10.1186/s10020-021-00384-2
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 up-regulates PD-L1 to promote HPV-positive cervical cancer via HER2/PI3K/AKT pathway

Abstract: Background HPV16 is the predominant cancer-causing strain that is responsible for over 50% of all cervical cancers. In this study, we aim to investigate the therapeutic effect of heat shock protein 90 (Hsp90) knockdown on HPV16+ cervical cancer progression and the underlying mechanism. Methods The transcript and protein expression of Hsp90 in normal cervical and HPV16+ cervical cancer tissues and cell lines were detected by qRT-PCR, immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…It has been demonstrated that the PI3K/AKT pathway is an important cellular signaling pathway involved in a variety of cellular activities, including cell migration, proliferation, and survival (W. Dong et al, 2018 ; Guo et al, 2021 ; Zeng, He, Li, & Wang, 2021 ). Previous studies have indicated that PI3K could aggravate impairment of HUVECs and angiogenesis, indicating a potential target for wound healing ( Hunter et al, 2019 ; M.; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the PI3K/AKT pathway is an important cellular signaling pathway involved in a variety of cellular activities, including cell migration, proliferation, and survival (W. Dong et al, 2018 ; Guo et al, 2021 ; Zeng, He, Li, & Wang, 2021 ). Previous studies have indicated that PI3K could aggravate impairment of HUVECs and angiogenesis, indicating a potential target for wound healing ( Hunter et al, 2019 ; M.; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, Hsp90 levels did not vary in lobular neoplasia of the breast [ 61 ], while Hsp90 positive cells were significantly increased in invasive breast carcinoma [ 62 ], again indicating a role of Hsp90 in promoting malignancy. Hsp90 overexpression has been documented as a potential diagnostic marker in hepatocellular carcinoma [ 63 ]; cervical [ 64 ], colorectal [ 65 ], and breast [ 62 ] cancers; melanomas [ 66 ]; leiomyosarcomas [ 66 ]; gastrointestinal stromal tumors (GIST) [ 66 ]; and malignant peripheral nerve sheath tumors [ 66 ]. Tissue Hsp90 up-regulation was correlated with higher risk GIST and extragastric locations, and served as an independent predictor of recurrence in patients with GIST after complete surgical resection [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combined inhibition of Hsp90 and CDC37 was efficient in abrogating the phosphorylation of Akt in mutant BRAF colon cancer cells [ 82 ]. Conversely, other studies highlight the suppression of cellular proliferation, migration, and progression through deactivation of the PI3K/Akt pathway by Hsp90 knockdown or inhibition in colorectal [ 96 ], gastric [ 97 ], osteosarcoma [ 98 ], ovarian [ 99 ] and cervical [ 64 ] cancers. The discrepancy in the results may lie in the type of tissue, type of cancer and the cell lines that were used.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HSP90 binds to a variety of cell surface receptors and triggers signalling pathways that lead to malignancy. Zheng et al found that HSP90 can interact with HER2 to activate the PI3K/AKT signalling pathway thereby upregulating PD‐L1 expression and promoting cervical carcinogenesis (Zeng et al, 2021). Zhang et al found that inhibition of HSP90 inhibits HIF‐1α/VEGF/VEGFR‐2 mediated angiogenesis (Zhang et al, 2020).…”
Section: Classification and Structure Of Hsp90mentioning
confidence: 99%